Training future music art teachers to use ethnic-family traditions in overcoming war trauma in school youth - Rastrygina, Alla; Klepar, Maria (Professional Art Education, 2025)
The article considers the problem of training future music art teachers to use ethnic family traditions in overcoming war trauma in school youth. An analysis of modern scientific research in the field of ethnopedagogy, art history and psychology is presented. The content and structure of training a specialist-musician capable of trauma-informed assistance through art to overcome post-traumatic psycho-emotional disorders in schoolchildren are analyzed. The main directions of training future music art teachers for trauma-informed assistance through ethnic-family traditions on pedagogical principles are identified. It is proven that the phenomenon under study works more effectively according to the cross-cutting principle, since it is integrated into the educational process at the content, methodological and practical levels. The possibilities of its effective use in art and pedagogical education are revealed. The possibilities of using components of trauma-informed art in future professional activities by university students are outlined. The importance of creating safe environment for schoolchildren based on trust, mutual understanding, and art-communication interaction through ethnic-family traditions is emphasized.